Transition and Transformation of the Slovak Society and Slovak Identity - Pondelíková, Ivana (Acta humanitarica academiae Saulensis, 2023)
The aim of this paper is to disseminate partial results of the Europe for Citizens / Share EU – Shaping of the European citizenship in the post-totalitarian societies: Reflections after 15 years of European Union enlargement project. The project focuses on linking the educational process, historical memory, and social change 15 years after EU enlargement. Based on in-depth interviews, we have examined the transformation of Slovak society since the Velvet Revolution (1989) and joining EU (2004). The focus is given to the historical background that led to the change of a regime. The transformation to a democratic society resulted in the formation of a new Slovak identity, which was examined through Hofstede’s cultural dimensions. Respondents provided facts, thoughts, and their views of living in Slovak society since these two significant milestones.